Analisis Input-Output COVID-19: Mengukur Dampak Ekonomi Kebijakan Penanganan Pandemi COVID-19 di Indonesia - I Gede Putu Dharma Yusa (Politeknik Statistika STIS, 2021)
Policies for handling the COVID-19 pandemic that limit mobility had an impact on economic performance. Restrictions on a certain sector will have an impact to the others. Therefore, to measure it, it is necessary to have a tool that describes the linkages between economic sectors comprehensively. This study used restriction and extraction Input-Output Table approach to answer these problems, by measuring changes in output and income that occur according to restriction scenarios. There are three scenarios designed: limiting the working age of Work From Office (WFO), setting the WFO and Work From Home (WFH) system, and limiting working hours. The results, limiting the working age of WFO as well as setting the WFO and WFH systems are still able to increase the output and income of workers up to 11,16 percent and 8,85 percent respectively. Meanwhile, in the scenario of limiting working hours, there is a decrease in the output and income of workers by 23,87 percent and 38,78 percent respectively.